New insights into ginsenoside Rg1 regulating the niche to inhibit age-induced germline stem cells depletion through targeting ECR/BMP signaling pathway in Drosophila. - Fu, B.; Ma, R.; Liu, F.; Chen, X.; Wang, M.; Jin, W.; Zhang, S.; Wang, Y.; Sun, L. (Aging, 2024)
The age-induced imbalance in ecological niches leads to the loss of GSCs, which is the main reason for ovarian germline senescence. Ginsenoside Rg1 can delay ovarian senescence. Here, we shed light on new insights of ginsenoside Rg1 in regulating the niche to maintain GSCs self-renewal and discussing related molecular mechanisms. The differences among GSC number, reproductive capacity of naturally aging female Drosophila after ginsenoside Rg1 feeding were analyzed by immunofluorescence and behavior monitoring. The expressions of the active factors in the niche and the BMP signaling were analyzed through Western blot and RT-qPCR. The target effect was verified in the ECR mutant and combined with the molecular docking. Ginsenoside Rg1 inhibited the age-induced reduction of the GSCs number and restored offspring production and development. Ginsenoside Rg1 promoted the expression of anchor proteins E-cadherin, stemness maintenance factor Nos and differentiation promoting factor Bam, thereby GSCs niche homeostasis was regulated. In addition, ginsenoside Rg1 was bound to the LBD region of the hormone receptor ECR. Ginsenoside Rg1 promotes the regeneration of GSCs by targeting the ECR to increase pSmad1/5/8 expression and thereby activating the BMP signaling pathway. In addition, ginsenoside Rg1 maintenance of niche homeostasis to promote GSCs regeneration is dependent on ECR as demonstrated in ECR mutants. Ginsenoside Rg1 regulated the ecological niche homeostasis of GSCs and promoted the regeneration of GSCs by targeting the ECR/BMP signaling pathway in hormone-deficient states in aging ovaries. It is of great significance for prolonging fertility potential and delaying ovarian senescence.